Customer Satisfaction of Bangladesh Railway E-Ticketing System:: A Gender Perspective (Bangladesh Journal of Public Administration, 2021)
E-ticketing service is one of the most popular innovations in the rail transportation service. Considering the significance of the service, the study aims to explore customer satisfaction of the e-ticketing system of the Bangladesh Railway. It also investigates the gender perspective in regards to the service quality dimensions. A cross-sectional study was conducted among 361 respondents, followed by a quantitative approach. A structured questionnaire was used to survey the passengers from different railway stations in Dhaka City. The findings showed that the service quality indicators such as well customized website (ß= .130, p value< 0.05), ease of using the website (ß = .339, p value